Efektivitas Metode Fenton-TiO2-UV Terhadap Degradasi Warna dan Chemical Oxygen Demand Pada Pengolahan Palm Oil Mill Effluent - Teguh, Dedi; Hanifah, Windia; Cendekia, Devy; Phelia, Arlina; Sari, Nita Pita; Adib, Asraf Wa (Politeknik ATI Padang, 2024)
The palm oil industry produces POME (Palm Oil Mill Effluent) liquid waste. POME is generally brownish, has an odor, and contains dissolved and suspended solids in the form of colloids and oil residue with a high Chemical Oxygen Demand (COD) content. Currently, the POME processing system still uses a conventional system known as the open pond system. This research aims to reduce the burden of organic materials related to removing COD levels, and color. It can solve the technical and operational obstacles of conventional processing systems. One of the extensive efforts to process POME is to develop Fenton-based photocatalytic technology, namely the Fenton-TiO2-UV method. Photocatalytic technology has several general processes involving semiconductor photocatalysts such as TiO2 and photon (UV) energy sources. In this study, the Fenton-TiO2-UV method was used with variations in the Fenton molar ratio of 1:100, 1:200, 1:300 (v/v), reaction times of 30, 60, and 90 minutes with TiO2 concentration 0.6% and uses 2 UV lamps (15 watts). This study achieved the maximum color degradation percentage at a Fenton molar ratio of 1:100 with a reaction time of 30 minutes, namely 95.28%. Meanwhile, the maximum COD degradation percentage was achieved at a Fenton molar ratio of 1:100 with a reaction time of 90 minutes, namely 98.88%.